Ujaran Kebencian Pada Kolom Komentar Akun Tiktok Team Mafia Pentol Pusat - Laily, Frivia Munjidatul; Kurniyah, Heva Risnaini; Suryani, Yunita (STAI Denpasar Bali, 2023)
Tiktok is one of the online social media that is currently being widely used, tiktok can access videos, the videos that are made vary depending on the intent and purpose that the account owner wants to convey. Including crimes in language, one of which is hate speech received by the account of the central pentol mafia team in the comments column of the post. The data in this study are in the form of sentences that refer to hate speech in the comments column of the central pentol mafia team tiktok account. Data collection techniques were carried out from observations and analysis of language crimes. By using descriptive method. Based on the analysis of the data carried out, it was found that the hate speech in the comments column of the central pentol mafia team's tiktok account had an action dimension, including: (1) satirizing accompanied by ridicule and disgrace of the interlocutor in public. (2) accusing a thing or action. (3) criticizing the speech partner's actions.